PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA LANJUTAN PADA SISWA KELAS VB UPTD SD INPRES SIKUMANA 3 KOTA KUPANG - Tobe, Marlin Rosita; Sampe, Markus; B N Benu, Adam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the advanced reading skills of Grade VB students at UPTD SD Inpres Sikumana 3, Kupang City, through the application of the Project-Based Learning (PjBL) model. The background of this research is based on students' difficulties in understanding reading materials, as evidenced by their inability to identify main ideas and conclude the content of the text. Students often read the text without a deep understanding of its meaning. This research is a Classroom Action Research (CAR) conducted in one cycle, consisting of planning, implementation, observation, and reflection. The subjects of this study were 24 students of Grade VB at UPTD SD Inpres Sikumana 3, Kupang City. Data collection techniques included observation, tests, and documentation. The intervention involved providing reading texts to students, followed by group assignments to create a project based on the content of the text. The results showed that the application of the Project-Based Learning (PjBL) model significantly improved students' advanced reading skills. This was demonstrated by an increase in the percentage of students passing the reading test: from 16.67% (4 out of 24 students) in the pre-test to 87.5% (21 out of 24 students) in the post-test. Furthermore, there was an increase in student engagement during the learning process. The PjBL model proved to be effective in improving advanced reading skills, which subsequently impacted student learning outcomes. In conclusion, the Project-Based Learning (PjBL) model effectively enhances the advanced reading skills of Grade VB students at UPTD SD Inpres Sikumana 3, Kupang City.